Selection of a new auxotrophic mutant by transformation-mediated gene disruption in Podospora anserina. - A. Sainsard-Chanet; O. Begel (Fungal Genetics Reports, 1991)
A mutant auxotroph for methionine was isolated in Podospora anserina during a transformation experiment. The transforming plasmid (pPAaURA5) consisted of a 1.55 kb nuclear DNA fragment of Podospora containing the URA5 gene (Begueret et al. 1984, Gene 32:487-492; Turq and Begueret 1987, Gene 53:201-209), and most (2.06 kb) of the Podospora intronic alpha mitochondrial sequence (Osiewacz and Esser 1984, Curr. Genet. 8:299-305) cloned in the pUC18 vector.